The Unconscious in Philosophy, and French and European Literature : Nineteenth and Early Twentieth Century. - Vial, Fernand. (Value Inquiry Book Series, 2009)
This book traces the idea of the unconscious as it emerges in French and European literature. It discusses the functioning of the normal unconscious mind and provides examples of the abnormal unconscious in poems and literature. Psychiatric cases as they are understood today are illustrated as mirrored in literature describing the functioning of the disturbed mind.